System dynamics research of bad and good decision processes and outcomes - Woodside, Arch (2016)
Copyright © 2016 by Emerald Group Publishing Limited.Business realities include delays, unintended downstream consequences, exponential versus linear relationships, 'hidden demons,' and virtuous and viscous feedback cycles. Executives often respond to these realities by applying nearsighted short-term solutions that contribute to long-run business failure. We provide core propositions and a framework for causal mapping and testing 'micro-worlds' of real-life marketing-buying realities. A microworld is a set of explicit assumptions about how things get done, that is, how each variable in a marketing-buying system relates to other variables in the system. The framework suggests applying eight steps linking systems-thinking cause mapping, policy mapping, and systems dynamics modeling. The chapter reviews case research studies that apply the eight steps. Modeling system dynamics of business relationships aims to run simulations of the resulting microworld model of a specific reality; the main aim goes beyond description and explanation to offer prescriptions that reduce the occurrence of viscous cycles and encourage decisions leading to virtuous cycles. Hopefully, this chapter serves to awareness and use of system dynamics tools among case study researchers and executives in business and industrial marketing.